Market Risk Management Practices of the Indian Banking Sector: An Empirical Study - Brahmaiah, Bezawada (International Journal of Economics and Financial Issues, 2022)
The primary objective of this paper is to examine the market risk and liquidity risk management techniques and practices followed by the Indian scheduled commercial banks (SCB) consisting of public sector banks (PSBs) and private sector banks (PVSBs) for five years from 2016-17 to 2020-21. The other objective is to compare market and liquidity risk management practices between the public sector banks (PSBs) and private sector of banks (PVSBs). The other purpose of the study is to review the strategies adopted by the SCBs in risk management practices. To study the risk management practices, six largest banks each from PSBs and PVSBs are taken for sample study. This study finds that the SCBs are facing credit risk, market risk (Interest rate risk, foreign exchange risk, commodity price risk and equity price risk,) liquidity risk and operational risk. It also finds that the PSBs are better reporting and presenting their risk management practices in their annual reports than that of PVSBs in risk identification, risk assessment and risk analysis. The results indicate that there is no significant difference between the PVSBs and PSBs in the policies and practices of market risk and liquidity risk assessment, evaluation, monitoring risk controlling and risk taking. This paper will be relevant and value to those interested in research in the risk management banking industry. This is a descriptive research based on secondary data.